ANALYSIS OF BIOGAS UTILIZATION AS NVIRONMENTALLY FRIENDLY ELECTRICAL ENERGY IN TANA TORAJA (International Conference on Social and Islamic Studies, 2021)
Biogas produced from livestock and agricultural waste is used by the community as asubstitute for natural gas energy and as a substitute for electrical energy to provide gas needs for gas stoves and household electrical energy needs in Tana Toraja Regency. This study aims to analyze the level of community involvement in Tana Toraja Regency in utilizing biogas as an alternative energy source and a solution for livestock and agricultural waste. Furthermore, by using a quantitative approach, this research also aims to identify the impact of using biogas as an alternative energy for the community from an economic, social and environ mental perspective. Biogas is one solution to the scarcity of posil energy sources and is an environmentally friendly alternative energy source. This advantage makes Biogas an energy source that has good prospects as an alternative energy substitute for non-renewable energy in Indonesia, which is currently experiencing an energy crisis, which is characterized by increasingly scarce and high fuel prices which have an impact on the higher production costs of power plants. The existence of renewable energy is something that is very important to meet energy needs in Indonesia.